Does the barnacle settlement pattern affect ship resistance and powering?. (February 2020) - Uzun, Dogancan; Ozyurt, Refik; Demirel, Yigit Kemal; Turan, Osman
Highlights: A novel chaotic barnacle settlement pattern was designed by using 3D printed barnacles. The effect of barnacle settlement pattern was investigated by comparing the standard settlement pattern and the developed settlement pattern. Added resistances, increases in effective power and reductions in ship speed for different types of ships were predicted. The study supports decision makers by helping them to decide on the effective ship hull cleaning and maintenance schedule. Abstract: Predictions of increases in ship frictional resistance and powering were made for a range of barnacle fouling conditions. A series of towing tests were conducted using flat plates systematically covered with 3D printed barnacle tiles. The tests were set up to investigate the effect of barnacle settlement on the resistance and effective power of the ship. Therefore, a chaotic settlement which is called natural settlement, was designed to represent real barnacle settlement in nature. An extensive comparison was made between this natural settlement and the settlement that was designed in accordance with the standards. The drag coefficients and roughness functions values were determined and full-scale ship resistance and powering were estimated for six different ships at their cruise speed by using boundary layer similarity law. In addition, decreases in cruising speed due to barnacle fouling at fixed effective power were estimated as part of the case studies. The results indicate that settlement pattern caused up to ~10.5% difference in frictional resistance and ~6.7% difference in powering at cruise speeds whereas this settlement pattern caused up to ~20.5% speed reduction at fixed effective power.